Interleukin-6 levels and their haplotypes are associated with serological autoantibodies status and clinical activity in rheumatoid arthritis - Flores-Castro, Ma. Natividad; Falfán-Valencia, Ramcés; Briceño, Olivia; Gutiérrez-Pérez, Ilse Adriana; Zaragoza-García, Oscar; Pérez-Rubio, Gloria; Morales-Martínez, Cristina; Guzmán-Guzmán, Iris Paola (Frontiers in Immunology, 2025)
IntroductionInterleukin-6 (IL-6) plays an important role in the pathogenesis, progression, and severity of rheumatoid arthritis (RA). High levels of IL-6 are involved in the maintenance of inflammation in the synovium and the development of new blood vessels in the inflamed synovium, contributing to pannus formation. In the present study, we aimed to investigate the relationship of IL-6 polymorphisms/ haplotypes with RA in Mexican patients and on circulating levels of IL-6 and the clinical features of the disease.MethodsA total of 225 patients with RA and 362 healthy controls were recruited. Patients’ clinical features were collected, and inflammatory and serological parameters [anti-cyclic citrullinated peptides (anti-CCPs) and rheumatoid factor (RF)] were assessed. All subjects were genotyped for IL-6 polymorphisms (rs1800797, rs1800796, and rs1818879) using real-time polymerase chain reaction (PCR) with TaqMan probes. Circulating levels of IL-6 were measured by commercial ELISA (enzyme-linked immunosorbent assay) kits.Results and discussionOur results show that the GGG haplotype of the IL-6 gene is associated with a serological status of double-positive autoantibodies [odds ratio (OR) = 2.09, p = 0.009], as well as with a double-positive high autoantibodies status (OR = 2.08, p = 0.04), although a marginal association was shown to RA susceptibility (OR = 1.34, p = 0.050). Polymorphisms and haplotypes were not associated with serum levels of IL-6. However, serum levels of IL-6 ≥27.6 pg/mL were associated with clinical features of RA severity, such as morning stiffness ≥30 min (OR = 1.83, p = 0.001), HAQ-DI ≥1 (OR = 2.73, p=0.009), DAS28-ESR ≥3.2 (OR = 3.63, p = 0.002), and hsCRP ≥10 mg/L (OR = 6.35, p < 0.001). This study provides evidence of the relationship between IL-6 haplotypes, circulating levels of IL-6, and clinical features and serological status to autoantibodies in patients with RA from Mexico.